The geometry of the magnetic field in the central molecular zone measured by PILOT - A. Mangilli; J. Aumont; J.-Ph. Bernard; A. Buzzelli; G. de Gasperis; J. B. Durrive; K. Ferrière; G. Foënard; A. Hughes; A. Lacourt; R. Misawa; L. Montier; et al. (Astronomy & Astrophysics (A&A; EDP Sciences), 2019)
We present the first far infrared (FIR) dust emission polarization map covering the full extent of Milky Way’s central molecular zone (CMZ). The data, obtained with the PILOT balloon-borne experiment, covers the Galactic center region –2° < ℓ < 2°, –4° < b < 3° at a wavelength of 240 μm and an angular resolution of 2.2ʹ. From our measured dust polarization angles, we infer a magnetic field orientation projected onto the plane of the sky (POS) that is remarkably ordered over the full extent of the CMZ, with an average tilt angle of ≃ 22° clockwise with respect to the Galactic plane. Our results confirm previous claims that the field traced by dust polarized emission is oriented nearly orthogonally to the field traced by GHz radio synchrotron emission in the Galactic center region. The observed field structure is globally compatible with the latest Planck polarization data at 353 and 217 GHz.
Keywords: Central Molecular Zone; Galactic Center; magnetic field geometry; FIR polarization; PILOT balloon experiment; dust polarization; type of access: open access